A Hardware-in-the-Loop Co-simulation of Multi-modal Energy System for Control Validation - Liu, Diran; Hering, Dominik; Carta, Daniele; Xhonneux, Andre; Muller, Dirk; Benigni, Andrea (IECON 2021 – 47th Annual Conference of the IEEE Industrial Electronics Society, 2021)
In this paper, we present a Hardware-in-the-Loop (HIL) co-simulation framework to test multi-modal energy systems. The framework has been tested using as an example a section of the Living Lab Energy Campus (LLEC) of the Forshungszentrum Jülich (DE). A master algorithm has been developed to orchestrate the two components of the co-simulation platform: the real-time simulation of the power network running on OPAL-RT, and the real-time simulation of the low-temperature district heating (LTDH) network using Functional Mock-up Units (FMU) on a custom cluster. The master algorithm also coordinates the exchange of information between the real-time simulators and the device under test. The device under test is composed of a cloud-based model predictive control (MPC) -that operates on the heat pumps in the LTDH network - and an MQTT broker. The results show the co-simulation is successful and the framework can validate the control algorithm.